Efficacy of Qishen Yiqi Drop Pill for Chronic Heart Failure: An Updated Meta-Analysis of 85 Studies - Hao Wang; Lixia Li; Xiaochun Qing; Shouyan Zhang; Shulong Li (Hindawi-Wiley, 2020)
Background. Despite evidence for beneficial effects of Qishen Yiqi Drop Pill (QSYQ) on congestive heart failure, the majority of studies are based on insufficient sample sizes. The aim of this study was to evaluate the therapeutic effects of QSYQ using a meta-analysis approach. Methodology/Principal Findings. All relevant studies published before December 31, 2019, were identified by searches of various databases with key search terms. In total, 85 studies involving 8,579 participants were included. The addition of QSYQ to routine Western medicine increased 6-minute walking distance (SMD=2.08, 95% CI: 1.72-2.44, p<0.001), left ventricular ejection fraction (SMD=1.05, 95% CI: 0.87-1.23, p<0.001), and cardiac index (SMD=1.44, 95% CI: 0.92-1.95, p<0.001) and reduced brain natriuretic peptide (SMD=−2.28, 95% CI: -2.81 to -1.76, p<0.001), N-terminal prohormone of brain natriuretic peptide (SMD=−2.49, 95% CI: -3.24 to -1.73, p<0.001), left ventricular end-diastolic dimensions (SMD=−0.92, 95% CI: -1.25 to -0.59, p<0.001), and left ventricular end-systolic dimensions (SMD=−0.55, 95% CI: -0.89 to -0.21, p<0.001). The results were stable in subgroup analyses and sensitivity analyses. Conclusions. Our current meta-analysis indicated that QSYQ combined with Western therapy might be effective in CHF patients. Further researches are needed to identify which subgroups of CHF patients will benefit most and what kind of combination medicines work best.